2012
DOI: 10.2119/molmed.2011.00463
|View full text |Cite
|
Sign up to set email alerts
|

Implication of the miR-184 and miR-204 Competitive RNA Network in Control of Mouse Secondary Cataract

Abstract: The high recurrence rate of secondary cataract (SC) is caused by the intrinsic differentiation activity of residual lens epithelial cells after extra-capsular lens removal. The objective of this study was to identify changes in the microRNA (miRNA) expression profile during mouse SC formation and to selectively manipulate miRNA expression for potential therapeutic intervention. To model SC, mouse cataract surgery was performed and temporal changes in the miRNA expression pattern were determined by microarray a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 68 publications
2
23
0
Order By: Relevance
“…EMT is characteristic of TGFβ-induced anterior subcapsular cataract formation, a pathology also associated with reduced dosage of Pax6 [44][46]. Interestingly, secondary cataract has recently been associated with alterations in miR-204 expression [47]. With this in mind, it is possible that part of Pax6 's activity in inhibiting cataract formation is mediated by the activity of miR-204 in the lens and that restoration of miR-204 levels may prevent anterior subcapsular cataract formation.…”
Section: Discussionmentioning
confidence: 99%
“…EMT is characteristic of TGFβ-induced anterior subcapsular cataract formation, a pathology also associated with reduced dosage of Pax6 [44][46]. Interestingly, secondary cataract has recently been associated with alterations in miR-204 expression [47]. With this in mind, it is possible that part of Pax6 's activity in inhibiting cataract formation is mediated by the activity of miR-204 in the lens and that restoration of miR-204 levels may prevent anterior subcapsular cataract formation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, through in vitro studies, miR-204 has been associated with cell migration and invasiveness [15], [16], [17], [18], [19], [20]. However, it is completely unknown whether this miRNA has a similar function in cells of living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…23 Recent studies by Zhang et al 24 found that miR-204 downregulates SIRT1 and reverts SIRT1-induced EMT in gastric cancer cells. During the process of EMT, they found that the expression of miR-204 was decreased, and upregulation of miR-204 reverted EMT by targeting SIRT1.…”
Section: Discussionmentioning
confidence: 99%